A new photolabile protecting group based on a coumarin bearing a julolidine donor group : synthesis and photolysis studies - Piloto, Ana M. (2012)
Natural or synthetic 2H-benzopyran-2-ones (coumarins) have found a broad range of applications in diverse areas, being the subject of intense research in recent years also due to their capability to act as fluorescent markers, as well as photolabile protecting groups [1]. These groups have been investigated for the protection of functional groups in synthetic strategies, but also as phototriggers for the study of numerous processes in biotechnology and cell biology [1-3]. As part of the present research interests of the authors on the design, synthesis and application of O and N heterocycles as photocleavable protecting groups for the carboxylic and amine functions [1,4], it is now described the synthesis of 9-(chloromethyl)-2,3,6,7-tetrahydro-1H-pyrano[2,3-f]pyrido[3,2,1-ij]quinolin-11(5H)-one (a fused coumarin derivative) 1, and its evaluation in the photorelease of neurotransmitter amino acids 2 from the corresponding fluorescent caged compounds 3a-c. The synthesis of label 1 was carried out by a triisopropoxytitanium(IV) chloride-catalysed Pechmann condensation between 1,2,3,5,6,7-hexahydropyrido[3,2,1-ij]quinolin-8-ol (trivially known as hydroxy-julolidine) and 4-chloroacetoacetate, in toluene, under reflux conditions [5]. N-Benzyloxycarbonyl-protected glycine 2a, beta-alanine 2b and gamma-butyric acid 2c were derivatised at the C-terminus with the chloromethylated tag 1 in the presence of potassium fluoride [6] in DMF, at room temperature yielding the expected ester bioconjugates 3. These compounds, after fundamental photophysical characterisation, were subjected to photolysis in methanol/HEPES buffer solution (80:20) at different wavelengths of irradiation revealing a great potential in the photorelease of the neurotransmitters used.